Зарубіжний досвід функціонального визначення найвищої судової інстанції: порівняльно-правовий аналіз - Калараш, А. А.; Kalarash, A. A. (Правові новели. – 2019. – № 8, т. 2. – С. 13-21, 2019)
Здійснено порівняльно-правовий аналіз чинного законодавства деяких зарубіжних країн щодо порядку організації роботи Верховного суду як інституту судової влади. Вироблено загальні концептуальні підходи щодо розуміння функціонального визначення найвищої судової інстанції як гарантії верховенства права і довіри суспільства до судової влади.

The article is devoted to the comparative legal study of the current legislation of foreign countries, which determine the order of organization of the Supreme Court as the highest judicial body. The paper emphasizes that a striking example of the Anglo-Saxon model of the judicial system is the US judicial system, in which the leading role is determined by the Supreme Court – the highest court in the federal judicial system. With this in mind, the evolution of the formation of the powers of the US Supreme Court since its inception has been studied. It is noted that the judiciary was formalized and enshrined in one of the seven articles of the US Constitution, adopted July 4, 1776. It also focuses on the list of normative principles of the US Supreme Court and other federal courts. Attention is paid to defining the system of powers of the subjects of the US judicial system. The legal system of the Federal Republic of Germany occupies an important place in the RomanoGermanic legal system. It absorbed the traditions of Roman law and the legal heritage of the German state itself, which were embodied in national law. It is noted that in Germany the basis of judicial power is a set of judicial bodies of different jurisdiction, which are divided into general and special courts, as well as their powers. With regard to Italy, it is emphasized that there are courts of constitutional, general and special jurisdiction. In this context, the activity of the Supreme Court of Cassation of Italy as an independent body of the Italian judicial system is of particular interest for scientific research. In the framework of this comparative legal study, in order to determine the general patterns of functioning of the Supreme Court as an institution of the judiciary, it is useful to pay attention to the judicial system of an East Asian country such as China. In this regard, it is noted that the legal system of the People’s Republic of China is based on the Romano-Germanic tradition. China’s judicial system consists of general and special courts. The Supreme People’s Court of the People’s Republic of China belongs to the general courts together with the local people’s courts. As a result, having analyzed the positions of the judiciary of foreign countries, the main functions of the Supreme Court as an important institution of the judiciary in foreign countries are highlighted.

Проведен сравнительно-правовой анализ действующего законодательства некоторых зарубежных стран относительно порядка организации работы Верховного суда как института судебной власти. Выработаны общие концептуальные подходы к пониманию функционального определения высшей судебной инстанции как гарантии верховенства права и доверия общества к судебной власти.
Foreign experience of functional determination of the supreme judicial institution: comparative and legal analysis
Калараш, А. А. Зарубіжний досвід функціонального визначення найвищої судової інстанції: порівняльно-правовий аналіз / Калараш А. А. // Правові новели. – 2019. – № 8, т. 2. – С. 13-21. - DOI: https://doi.org/10.32847/ln.2019.8-2.02.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зарубіжний досвід; foreign experience; зарубежный опыт; Верховний суд; Supreme Court; Верховный Суд; судова система; judiciary; судебная система; законодавство; legislation; законодательство; США; USA; Німеччина; Germany; Германия; Італія; Italy; Италия; Китай; China